Conditions under which college students cease learning - Coldren, Jeffrey (Frontiers in Psychology, 2023)
Effective learning involves the acquisition of information toward a goal and cessation upon reaching that goal.  Whereas the process of learning acquisition is well understood, comparatively little is known about how or when learning ceases under naturalistic, open-ended learning conditions in which the criterion for performance is not specified.  Ideally, learning should cease once there is no progress toward the goal, although this has never been directly tested in human learners.  The present set of experiments explored the conditions under which college students stopped attempting to learn a series of inductive perceptual discrimination problems.  Each problem varied by whether it was solvable and had a criterion for success.  The first problem was solvable and involved a pre-determined criterion.  The second problem was solvable, but with no criterion for ending the problem so that learners eventually achieved a highly accurate level of performance (overlearning).  The third problem was unsolvable as the correct answer varied randomly across features.  Measures included the number of trials attempted and the outcome of each problem.  Results revealed that college students rarely ceased learning in the overlearning or unsolvable problems even though there was no possibility for further progress.  Learning cessation increased only by manipulating time demands for completion or reducing the opportunity for reinforcement.  These results suggest that human learners show laudable, but inefficient and unproductive, attempts to master problems they should cease.